From starch to bioactives: emerging trends in taro (Colocasia esculenta L.) research on composition, functionality, health benefits, and sustainable food potential - Tan, Yuan; Zheng, Feng-Jin; Lin, Bo; Chen, Jing; Verma, Krishan K.; Chen, Gan-Lin (Frontiers in Nutrition, 2025)
Taro (Colocasia esculenta L.), a globally significant root crop, has garnered renewed scientific interest due to its nutritional richness, bioactive compounds, and diverse functional applications. Recent studies have elucidated its unique composition, including high-quality starch with low glycemic potential, dietary fiber, polyphenols, i.e., flavonoids, anthocyanins, and potassium, calcium, iron minerals. Innovations in processing strategies, such as fermentation and thermal applications, have enhanced its digestibility while mitigating anti-nutritional factors like oxalates. Functionally, taro exhibits prebiotic, hypoglycemic, and hypocholesterolemic properties, attributed to its resistant starch and antioxidant activity. Taro corms starch (70%−80% on dry basis) contemplate as a cheapest abode for food industries due to its multiple functions in foods, such as stabilizer, emulsifier, fat substitute, and as filler agent too. It is rich in mucilage and starch granules, making it a highly digestible (99%) ingredient because of their small in size. Starch is a complex carbohydrate synthesized in some plant species, i.e., rice, wheat, potato, taro, elephant foot yam, maize, and others. Taro starches have higher phosphorus (0.407%), protein (5.605%) and ash (0.851%) contents than other tropical roots like tiger nut and sweet potato, but lower lipid content (0.283%). Taro has been found to contain several active compounds, such as resistant starch, mucilage, anthocyanins, hemagglutinin, non-starch polysaccharides, protein, tarin lectin, and others, which exhibit numerous beneficial properties, including antitumor, antimetastatic, antioxidant, and anti-inflammatory effects. Emerging evidence highlights its efficacy in modulating gut microbiota, reducing inflammation, and mitigating risks of metabolic disorders, such as diabetes and obesity. Furthermore, taro-derived bioactive compounds show promise in antimicrobial and anticancer applications. Advances in genomics and biofortification are driving sustainable cultivation and novel food approaches, including gluten-free products and functional food additives. Despite significant advancements, challenges remain in standardizing and scaling up these bioactive extraction processes for industrial applications. This review emphasizes taro's potential as a vital crop for food security and human health due to recent research advancements.